Development and Validation of RP-HPLC Method for the Simultaneous Estimation of Salbutamol Sulphate and Ambroxol Hydrochloride in Oral Liquid Dosage Form - Kumar, Rakesh; Bansal, Mukesh; Agarwal, Dilip (Asian Journal of Pharmaceutical Research and Development, 2021)
Pharmaceutical analysis is imported branch of science deals with to check the identity, strength, quality and purity of chemical and herbal compounds. Qualitative analysis of drugs and pharmaceutical compounds. Quantitative analysis is of much importance and done by various methods. One of the most accurate and precise methods is spectrophotometry which comprises the measurement of intensity of electromagnetic radiation emitted or absorbed by the compound. Another most popular method of for quantitative analysis is high performance liquid chromatography (HPLC). In the present article a RP-HPLC method was developed for the simultaneous determination of salbutamol sulphate and ambroxol hydrochloride in oral liquid doses form and validation of the developed method. Developed methods include selection of mobile phase, chromatographic method, and wavelength whereas validation involves the system suitability, accuracy, precision, linearity, reproducibility, robustness, specificity and solution stability of the developed method. The result showed that the developed method is the best suited to the simultaneous determination of salbutamol sulphate and ambroxol hydrochloride and validated as per the standards.